2012
DOI: 10.1074/jbc.m112.351262
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor β and Its Domains Interact with Casein Kinase 2, Phosphokinase C, and N-Myristoylation Sites of Mitochondrial and Nuclear Proteins in Mouse Brain

Abstract: Background: Estrogen receptor ␤ and its domain interact with a host of brain mitochondrial and nuclear proteins. Results: Estrogen receptor ␤ interacting brain mitochondrial and nuclear proteins have consensus motifs. Conclusion: Estrogen receptor ␤ interacts with casein kinase 2, phosphokinase C, and N-myristoylation sites present in mitochondrial and nuclear proteins. Significance: This might be useful to regulate estrogen-dependent gene regulation in brain for therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Studies have shown that mtERβ can increase mitochondrial DNA (mtDNA)–encoded transcription of cytochrome oxidase subunits I, III, and IV; increase respiration capacity; elevate antioxidant activity; and inhibit apoptosis . Using pull‐down assays and matrix‐assisted laser desorption ionization–mass spectroscopy, ERβ has been found in the mouse brain to interact with mitochondrial casein kinase 2 and phosphokinase C, which contribute to biogenesis of the mitochondrial translocase of the outer membrane and regulate ATP‐sensitive mitochondrial potassium channels, respectively . Additionally, it has been shown that mtERβ binds to estrogen response element (ERE)–like sequences in the D‐loop of mtDNA (Fig.…”
Section: Estrogen Acts Via the Estrogen Receptor Localized Within Mitmentioning
confidence: 99%
“…Studies have shown that mtERβ can increase mitochondrial DNA (mtDNA)–encoded transcription of cytochrome oxidase subunits I, III, and IV; increase respiration capacity; elevate antioxidant activity; and inhibit apoptosis . Using pull‐down assays and matrix‐assisted laser desorption ionization–mass spectroscopy, ERβ has been found in the mouse brain to interact with mitochondrial casein kinase 2 and phosphokinase C, which contribute to biogenesis of the mitochondrial translocase of the outer membrane and regulate ATP‐sensitive mitochondrial potassium channels, respectively . Additionally, it has been shown that mtERβ binds to estrogen response element (ERE)–like sequences in the D‐loop of mtDNA (Fig.…”
Section: Estrogen Acts Via the Estrogen Receptor Localized Within Mitmentioning
confidence: 99%
“…3A ) and/or (ii) MR co-regulators directly. For other SHRs like ERβ and GR it has been established that SHR co-regulators are phosphorylated by CK2 and thereby modulating transcriptional SHR activity 24 , 25 . So far, it is not known whether i) CK2-induced phosphorylation of MR-S459 alters the interaction with MR co-regulators, ii) MR-caveolin signaling and/or iii) whether known MR co-activators are regulated by CK2-induced phosphorylation directly which will be investigated in further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of further evidence associated with the diagnosis of breast cancer by MALDI TOF analysis of ERs highlights the issues associated with ER protein analysis in real biological samples. However, this method demonstrates excellent results for the visualization of protein expression ( 46 , 53 ), DNA methylation status ( 54 ), monitoring of ER interactions ( 55 , 56 ) and in searching for new biomarkers for breast cancer diagnosis ( 57 , 58 ).…”
Section: Maldi Tof As a Tool For Analysis Of Ersmentioning
confidence: 99%